Mitos Kala dalam Arsitektur Wolff Schoemaker pada Gedung Landmark Bandung - Ganesha Wibisana (PANTUN, 2020)
The interesting aspect of various architectural works of Wolff Schoemaker in Bandung city is the interaction between the sphere of Western and Eastern influence expressing full Indonesian ornamentation. This can be seen in the use of Kala’s head in the Landmark building. The figure is depicted with a face without a lower jaw placed on the building through a symmetrical shape, but with a dynamic ornament. The purpose of this research is to examine the meaning and influence of Kala’s head in Schoemaker’s architecture. This study is qualitative research using descriptive analysis methods. It explains the conception of the times in terms of form, characteristics and their translation in the myths of Javanese society. It was adopted in colonial buildings which made a cultural acculturation in architecture. The results of the analysis show that the Kala ornament in the building is influenced by the shape of the temples in the Central Java period. It has an identical shape to the Kala at the Gedong Songo temple and the Semar temple functioning as an antidote to negativity in the building.Keywords: Ornaments, Architecture, Kala, Wolff Shoemaker